Public Management and Administration Studies. Should we Include Marketind in Our Curricula? - José L. VÁZQUEZ; Dan LAZAR; Pablo GUTIÉRREZ; José L. PLACER (Transylvanian Review of Administrative Sciences, 2006)
As a consequence of continuous adaptation of public institutions to requirements of framing where they perform day by day, Public Management and Administration is behaving once and again as a “reinvented” discipline, aiming a new kind of rational, innovative public entities that focus their activities towards an effective achievement of their intended results and benefits. Concepts such as those of “efficiency”, “effectiveness”, “responsibility”, “organizational culture”, etc. are now not only applied to business disciplines, but also to Public Management and Administration. At this point, Marketing has proved to be an useful subject in PMA curricula, not only being in demand by students and syllabi designers, but also by experts in the public field. However, applying marketing techniques and procedures in the same way as used in private business is clearly nonsense. We must consider a proper “public marketing” or “public sector marketing” development. In this paper we debate on these issues, as well as present an overview into the situation of Spanish public universities offering PMA studies, just when they are facing the Bologna adaptation requirements. As a conclusion, some comments for reflection are suggested.